DİSİPLİNLERARASI YAKLAŞIMLARLA KÜRESEL SORUNLARI ANLAMLANDIRMAK: SOSYAL BİLGİLER EĞİTİMİNDE YENİ YÖNTEM ARAYIŞLARI - KARTAL, Taha (TURAN : stratejik arastirmalar merkezi, 2025)
Global problems, which are becoming increasingly complex on a global scale, have multidimensional structures that cannot be grasped by the knowledge area of only one discipline. In this context, it is clear that Social Studies education needs new method searches that can contribute to the processes of making sense of global problems and thinking focused on solutions. This conceptual study aims to examine the theoretical contributions of interdisciplinary approaches to the processes of analyzing, understanding and critically evaluating global problems in the context of Social Studies education. The study examines the epistemological foundations of interdisciplinary thinking, as well as the cognitive flexibility and holistic perspectives it provides in solving complex problems. Contemporary global problems such as global climate crisis, migration, social inequality, sustainable development and digitalization have been analyzed by establishing bridges between the knowledge clusters of disciplines such as history, geography, economics, political science and sociology. This approach supports students not only in acquiring knowledge but also in their skills of critical thinking, problem solving and developing a multidimensional perspective. In terms of method, this study is a qualitative research and was conducted using the literature review method. Theoretical models related to interdisciplinary education approaches were examined and the interdisciplinary competencies of current Social Studies curricula regarding global problems were analyzed. The research process is ongoing and it is planned to evaluate the findings in more depth and develop concrete suggestions for curricula. Preliminary findings show that current curricula have various limitations in terms of interdisciplinary competencies.